Strategi Pengembangan Usaha Ayam Ras Petelur Di Kecamatan Dua Pitue Kabupaten Sidenreng Rappang - Adelia, Dian; Sirajuddin, Sitti Nurani; Jusni, Jusni (Universitas Galuh, 2024)
This research aims to determine appropriate strategies for the development of layer chicken businesses in the Dua Pitue Sub-District of Sidenreng Rappang Regency. The study was conducted in the Dua Pitue Sub-District, Sidenreng Rappang Regency. Respondents for this research were selected through purposive sampling, consisting of approximately twelve informants. The research is categorized as descriptive quantitative research. It identifies internal and external factors, which are then analyzed using an internal-external (IE) matrix. The results from the IE matrix serve as a reference for formulating development strategies using a SWOT matrix. The research findings indicate that the IE matrix falls into cell V, representing concentration through horizontal integration. Subsequently, strategies are formulated in the SWOT matrix, resulting in actionable strategies for the development of layer chicken businesses in the Dua Pitue Sub-District of Sidenreng Rappang Regency as follows: 1) Encouraging production growth by increasing the population of layer chicken breeds; 2) Advocating government involvement in supporting layer chicken businesses; 3) Strengthening the role of field officers in the livestock sector to enhance farmers' competencies; 4) Encouraging private sector and banking participation in the development of layer chicken businesses; 5) Maintaining good customer relations through attractive services and offers; 6) Enhancing production through pest and disease control for sustainable business operations; 7) Optimizing business capital and improving business development capabilities.